Non–adherence and predictors in patients with schizophrenia on second generation antipsychotics at Amanuel Mental Specialized Hospital, Ethiopia - Melak Gedamu Beyene; Solomon Teferra; Teferi Gedif Fenta (PLoS ONE, 2025)
Background Schizophrenia is a chronic and profound mental disorder. Non–adherence to prescribed medication regimens is a major concern in the treatment of schizophrenia. This study aimed to investigate the prevalence, factors, and reasons contributing to non–adherence among Ethiopian patients with schizophrenia who are receiving second-generation antipsychotics (SGAs). Methods A hospital–based cross–sectional study was done at Amanuel Mental Specialized Hospital (AMSH) from 03/10/2022 to 31/8/2023. Data were collected using the drug attitude inventory-10 (DAI-10) tool. Analysis was conducted using Statistical Package for Social Sciences (SPSS) version 25. Univariate and multivariate binary logistic regression analyses were conducted. Results Most participants were male, (90.0%), and aged 26-40 years, (53.5%). Mean doses for risperidone and olanzapine prescribed were 4.9mg (±2.4) and 13.5mg (±5.0), respectively. Close to 40% of patients were khat (Catha edulis) users. The mean Positive and Negative Syndrome Scale (PANSS) total score was 71.1 ± 35.9 and the Clinical Global Impression-Severity (CGI-S) score was 3.42 ± 1.21. Around 31.4% of participants were non-adherent. Forgetfulness (31.73%) and stigma (27.31%) were the primary reasons cited for non–adherence. The multivariate binary logistic regression analysis revealed a significant association between non–adherence and several key factors. Patients with a PANS score equal to or greater than 71 (95% CI: 1.04, 3.80; p = 0.02), Patients categorized as having a moderate to markedly severe illness (95% CI: 1.1, 3.1; p = 0.024), duration of follow-up (DUP) (6-10) years (95% CI: 1.4, 129; p = 0.02), and age (26-40) years (95% CI: 0.3, 0.9; p = 0.04) were found to be statistically significant predictors of non–adherence. Conclusion The investigators recommended that counseling of the patients to highlight the importance of adherence, instituting regular and comprehensive symptom monitoring, tailoring interventions to address reasons for non-adherence, promoting early intervention and treatment initiation to reduce the DUP, and customizing interventions based on age-specific needs.